The Technique of Processing the Results of Skills Domain Assessment in the Field of Tahfidz at Islamic Boarding Schools - Wildan, M; Prastowo, Andi (Universitas Muhammadiyah Magelang, 2022)
The phenomenon of memorizing the Qur'an in Indonesia can be seen from the establishments of many tahfidz houses, Al-Qur'an huts or other names with the vision of creating a Qur'anic generation. However, with the large number of enthusiasts of the tahfidz program, it raises doubt about the quality of its graduates due to the tendency of institutions to prioritize quantity over quality,which cause the lack of supervision due to the imbalance between supervisors and tahfidz candidates. The purpose of this study is to analyze the specific strategy applied by one of the Tahfidz Islamic Boarding Schools about how they evaluate their students so that they can score a tahfidz who is not only mumtaz 30 juz but also have mutqin (strongly stick and correct) memorization. This research is located at Pondok Pesantren Al-Munawwir, Madrasah Huffadh Complex II, Krapyak Yogyakarta. Data collection techniques were documentation techniques, interviews, and direct observation. Data analysis used were data reduction, data presentation, and drawing conclusions or verification. The finding in this study is that the assessment is carried out every semester. This Qur'an memorization assessment is included in the assessment of abstract skills. The assessment mechanism is carried out by listening to the memorization of students who read their memorization in one time while observing the aspects that are assessed based on the assessment guidelines that have been formulated. This assessment technique is included in the type of performance test with the type of identification test. The technique for processing the assessment results is applied using a non-test instrument in the form of a rubric and using a rating scale. The aspects assessed include Adabiah, Muhafazah, and recitation. The weakness of the implementation of Imtihan is that there is no interpretation or judgment from the evaluation results for students who do not meet the assessment criteria or students who read their memorization incompletely. The evaluation model is an illustration of how to formulate an objective skill assessment instrument and determine the right aspects of the target without ignoring the principles of evaluation even though there are still some weaknesses in it.